STATE OF MODERN ECOLOGY OF UZBEKISTAN AND ACTIONS TO REDUCE ENVIRONMENTAL EMISSIONS - Egamberdiyeva L.N.; Bekmirzayev M. (Western European Studies, 2024)
THIS article discusses environmental problems in different regions of Uzbekistan and their solutions
Keywords: Uzbekistan; population; environment; pollution